PENDAMPINGAN PEMBUATAN SISTEM AKUNTANSI SEDERHANA PADA UMKM WARUNG KELONTONG DI KECAMATAN PANJATAN - Dinar Astriana; Hasim As’ari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to improve the ability of small and medium-sized grocery store owners to understand and implement simple accounting systems. The program also helps business owners create simple cash books and loan accounts, and fosters discussions between business finances and personal needs. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The activity was implemented through preparation, mentoring, and evaluation stages at Bu Astuti's Shop and Bu Tutik's Shop in Panjatan District. The results of the activity indicate that business owners are beginning to understand the importance of recording transactions regularly, are able to maintain cash records and simple accounting, and are beginning to separate the use of business funds from personal needs. The mentoring provided also helps business owners monitor cash flow, understand inventory conditions, and manage finances more systematically.